Does Parental Marital Status Matter in Male Adolescent's Smoking Behaviors? - Ramani, Andrei; Irianti, Astrid Salsabila; Prayogo, Mohammad Ardi Setia; Kusumawardani, Devi Arine (Universitas Airlangga, 2024)
Background: Globally, approximately 940 million male adolescents and 193 million female adolescents were classified as smokers in 2019. The global prevalence of smoking has continued to decline over the years, but the number of smokers remains high due to population growth. Consistently, reports from the Indonesia Demographic Health Survey (IDHS) and Indonesia Fundamental Health Research have shown an increase in the number of adolescent smokers in Indonesia. Objective: This study aimed to investigate the relationships between parental marital status, age of male adolescents, socioeconomic family status, and educational level of male adolescents with tobacco smoking behavior. Method: The research design employed was a secondary data analysis using the IDHS 2017 data with n = 5,863 male adolescent respondents. Results: Most respondents did not smoke, had married parents, were between 15-17 years old, came from low to very low socioeconomic backgrounds, and had an educational level of junior high school or lower. All variables (parental marital status, age, socioeconomic status, and educational level) were found to be associated with smoking behavior among male adolescents aged 15-19 years. Conclusion: Adolescents with divorced parents were at a significantly higher risk, approximately 1.3 times greater, for smoking tobacco compared to those from non-divorced families. Intrinsic factors (age and educational level) emerged as dominant factors in the tobacco smoking behavior of male adolescents.